Ultrasound Imaging of Muscle-tendon Architecture in Neurological Disease: Theoretical Basis and Clinical Applications - Chen, Na; Hu, Huijing; Li, Le (Current Medical Imaging, 2014)
Advances in muscle imaging have led to an increasing number of studies relating non-invasive measurements of muscle-tendon complex architecture parameters. Ultrasonagraphy has been shown to be a feasible method to measure muscle morphological changes after neurological diseases such as stroke, cerebral palsy, and spinal cord injury, thus, may help to enhance the understanding of the mechanism underlying the impaired motor function by the muscle level as well as to evaluate the functional improvement of the affected muscle after an intervention program.
Keywords: spinal cord injury